2007
DOI: 10.1093/pcp/pcm035
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rubisco Content in Transgenic Rice Transformed with the ‘Sense’ rbcS Gene

Abstract: Rice (Oryza sativa L.) plants with substantially increased Rubisco content were obtained by Agrobacteriummediated transformation with the rice rbcS sense gene under the control of the rice rbcS promoter. The primary transformants were screened for the ratio of Rubisco to leaf-N content, and the transformants with 4120% wild-type levels of Rubisco were selected. In the progeny of the selected lines of the transformants, the mRNA levels of one member of the rbcS gene family were increased from 3.9-to 6.2-fold, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
106
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 44 publications
8
106
0
1
Order By: Relevance
“…OsRBCS1 transcripts were not detectable (data not shown). This result was consistent with that of Suzuki et al (2007). The levels of OsRBCS2, OsRBCS3, OsRBCS4 and OsRBCS5 mRNAs increased in response to NH 4 NO 3 supply (Fig.1).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…OsRBCS1 transcripts were not detectable (data not shown). This result was consistent with that of Suzuki et al (2007). The levels of OsRBCS2, OsRBCS3, OsRBCS4 and OsRBCS5 mRNAs increased in response to NH 4 NO 3 supply (Fig.1).…”
Section: Resultssupporting
confidence: 88%
“…These results indicate that the expression of the rbcS multigene family members is differently regulated by N in rice. Suzuki et al (2007) reported that OsRBCS1 was only slightly expressed, and the expression of OsRBCS2, OsRBCS3, OsRBCS4 and OsRBCS5 was enhanced to the same relative degree with increasing N supply. In addition, the amino acid sequences except the transit peptide, deduced from rice four rbcS genes except for OsRBCS1, are 100% identical.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations